Oral Health Literacy - Adult Questionnaire: Psychometric Properties and its Influence on Oral Health Status of School Teachers in Bhubaneswar, India - Ramesh Nagarajappa; Ipsita Mahapatra; Dharmashree Satyarup; Sharmistha Mohanty (Association of Support to Oral Health Research (APESB), 2022)
Objective: To translate Oral Health Literacy - Adult Questionnaire from English to Odia language and test its psychometric properties and assess its influence on oral health status of school teachers. Material and Methods: A cross-sectional survey was performed among 400; 116 (29%) males and 284 (71%) female school teachers of Bhubaneswar. OHL-AQ questionnaire subsequent to being translated to Odia language utilizing World Health Organization recommended translation back translation protocol was then tested for the establishment of its psychometric properties with assistance from the selected expert panel of academicians. The oral health status of participants was assessed using the WHO oral health assessment form-2013. Chi-square, t-tests, one-way ANOVA, and linear regression were used for statistical analysis. Results: Internal consistency of OHL-AQ-O was acceptable with an alpha value of 0.70. Test-retest reliability showed almost perfect agreement (ICC=0.90, CI=0.85-0.93) indicating highly reliable translated scale (p=0.001). Overall mean oral health literacy scores were 13.02±1.86, with about 80% belonging to the high oral health literacy level group. Caries prevalence was 78%, with a mean DMFT of 3.04±2.55. Shallow pockets were absent majorly in teachers belonging to the high oral health literacy group (p=0.01). The multiple linear regression model depicted that only the teaching experience variable added significantly to the prediction (p=0.008). Conclusion: OHL-AQ-O questionnaire was found valid and reliable to measure OHL. Further application of the instrument in other communities and populations will support establishing the external validity of the OHL-AQ-O.